Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.15295/bmij.v9i2.1809
|View full text |Cite
|
Sign up to set email alerts
|

The meditating effect of brand love in the relationship between brand experience and brand equity

Abstract: The purpose of this study is to examine whether brand love has a mediating effect on the relationship between brand experience and brand equity. The research data were obtained from 503 participants between the ages of 18-24 in Istanbul. Face-to-face survey technique was used as a data collection method, quota sampling and convenience sampling methods were preferred as the sampling method. The collected data were tested using exploratory factor analysis, confirmatory factor analysis and structural equation mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 35 publications
1
11
0
1
Order By: Relevance
“…Humans can develop feelings for non-human objects, such as a brand. Brand love has three dimensions: passion, intimacy, and commitment (Akgözlü and Kılıç, 2021;Jebarajakirthy et al, 2021;Pontinha and Coelho do Vale, 2020). The following research has also revealed that consumers have feelings of love for the brands they use (Ahuvia et al, 2020;Santos and Schlesinger, 2021).…”
Section: Theoretical Reviewmentioning
confidence: 83%
See 4 more Smart Citations
“…Humans can develop feelings for non-human objects, such as a brand. Brand love has three dimensions: passion, intimacy, and commitment (Akgözlü and Kılıç, 2021;Jebarajakirthy et al, 2021;Pontinha and Coelho do Vale, 2020). The following research has also revealed that consumers have feelings of love for the brands they use (Ahuvia et al, 2020;Santos and Schlesinger, 2021).…”
Section: Theoretical Reviewmentioning
confidence: 83%
“…Between consumers and brands, there is a bond like a relationship between humans, so brands can be called active partners. This is an application of the concept of brand loyalty and brand personality (Akgözlü and Kılıç, 2021;Kim et al, 2021;Shin et al, 2022;Xu and Jackson, 2019). Humans can develop feelings for non-human objects, such as a brand.…”
Section: Theoretical Reviewmentioning
confidence: 99%
See 3 more Smart Citations